Demography of remarriage and fertility desire among women receiving antiretroviral therapy in South West Nigeria (2021)
Background: In view of sociocultural norms surrounding marriage and childbearing in South West Nigeria, fertility desire may be stronger among remarried women living with HIV. This article describes the characteristics of remarriage and its relationship to fertility desire. Method: A cross-sectional study was conducted among HIV-positive women aged 18–49 years at the Antiretroviral Treatment (ART) clinic, College of Medicine/University College Hospital, Ibadan, Nigeria between November and December 2015. Data were analysed using descriptive statistics and generalised linear models. Results: Overall, 123 (17.3%) of 711 women had experienced remarriage. Significant factors among remarried women were a lack of formal education (ORadj = 3.35, CI: 1.46–7.72); polygamous family (ORadj = 2.65, CI: 1.71–4.12), and serodiscordant union (ORadj = 1.97, CI: 1.14–3.41). Fertility desire was expressed by 410 women (57.7%). After controlling for demographic, socio-economic, and HIV-care characteristics, remarried women were 2.5 times as likely to have fertility desire compared to their counterparts who never remarried (ORadj = 2.49, CI: 1.43–4.33). Younger age was significantly associated with higher odds of fertility desire. Other factors negatively associated with fertility desire were education (ORadj = 0.30, CI: 0.12–0.74) and number of surviving children (ORadj = 0.28, CI: 0.22–0.34). Conclusion: HIV-care and treatment programmes need to pay attention to reproductive concerns, especially among women in second and higher order marriages.